2021
DOI: 10.1016/j.ijscr.2021.105650
|View full text |Cite
|
Sign up to set email alerts
|

Castleman disease: A single-center case series

Abstract: Highlights Castleman disease is an overgrowth of lymphatic cells, usually in the chest or abdomen. Multicentric Castleman disease affects lymphatic cells throughout the body. HHV-8 and HIV have been associated with multicentric Castleman disease. Unicentric Castleman disease affects a single group of lymph nodes. Centricity is considered the most important indicator of patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
2
4
0
2
Order By: Relevance
“…Although Pribyl et al [ 5 ] reported a marginal female predominance among patients with UCD, CD generally affects both sexes equally [ 1 , 13 ]. We found a significant female predominance among our patients with UCD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Pribyl et al [ 5 ] reported a marginal female predominance among patients with UCD, CD generally affects both sexes equally [ 1 , 13 ]. We found a significant female predominance among our patients with UCD.…”
Section: Discussionmentioning
confidence: 99%
“…Castleman disease (CD), also known as angiofollicular lymph node hyperplasia or giant lymph node hyperplasia, was first described in 1954 [ 1 , 2 , 3 , 4 ]. The two main histological subtypes are the hyaline vascular and plasma cell variants, and a mixed variant is seen occasionally [ 5 ]. It is further classified as unicentric CD (UCD) or multicentric CD (MCD) according to the anatomical distribution of the disease and the number of lymph nodes involved [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unicentric Castleman’s disease, which mimic PPP, usually shows well-circumscribed and homogenous masses in mediatum with intense reinforcement on enhanced CT scan. Nevertheless, Unicentric Castleman’s disease predominantly consists of the hyaline vessel variant (90%) ( 19 ). Histopathology is the only method to make a definitive diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other findings include organomegaly, mainly hepato/splenomegaly, renal dysfunction, and respiratory complications. These individuals tend to have increased inflammatory markers, particularly serum CRP, along with anemia, thrombocytopenia, and characteristic hypergammaglobulinemia [2,4,5,8,14]. POEMS and TAFRO constitute the most severe forms of MCD and, if left untreated, can lead to life-threatening multiple organ dysfunction syndrome (MODS) [7].…”
Section: Discussionmentioning
confidence: 99%